A clinical case of a successful step-by-step treatment of a patient with a dissecting aneurysm of the ascending aorta involving the trunk of the left coronary artery - Aleksandr V. Bocharov (Eco-vector, 2021)
Background: The presented clinical case shows a version of successful step-by-step medical care for a patient with a dissecting aneurysm of the ascending aorta involving the trunk of the left coronary artery in a vascular center without a cardiac surgical support. Clinical case description: The patient was admitted to the Kostroma Regional Vascular Center with the symptoms of Acute Coronary Syndrome. During the examination in the clinic, the diagnosis of acute coronary syndrome with ST segment elevation was confirmed, and a dissecting aneurysm of the ascending aorta was also revealed. According to emergency coronary angiography, the dissection of the left coronary artery trunk was visualized, and the left coronary artery trunk was successfully stented with a bare metal stent. Later, the patient was transferred to a federal center, where aortic prosthetic reconstruction was performed. Conclusion: In patients with a dissecting thoracic aortic aneurysm involving the trunk of the left coronary artery and acute myocardial damage, who are admitted to a vascular center without a cardiac surgery support, the following step-by-step treatment strategy is likely to be effective: stenting the trunk of the left coronary artery with a bare metal stent and a further transfer to a center of cardiac surgery for a surgical treatment.